Isolation, Characterization, and Production of Lipase from Indigenous Fungal for Enzymatic Interesterification Process - LISA PRATAMA; IS HELIANTI; ANI SURYANI; BUDIASIH WAHYUNTARI (Microbiology Indonesia, 2017)
Lipase catalyses hydrolysis and esterification of lipids. The purpose of this research was to  obtain lipase producing indigenous fungi, to identify the selected fungi, to study optimum temperature and pH of the enzyme activity, as well as the  enzyme ability in interesterification reaction. The isolates used in the experiment were isolated from tempeh, oncom and BPPT laboratory culture collection. The results showed that three fungal isolates which isolated, tempe and oncom and  an isolate of BPPT-CC were positive produced lipase after qualitative assay using Rhodamine B, olive oil and PVA. The morphology identification of the isolates, revealed that R isolate was  Aspergillus sp, T isolate was Neurospora sp. and O isolate was Rhizopus sp. Upon quantitative assay from determination of the media and time production, potato dextro broth (PDB) with olive oil 2% in 48 hours fermentation showed the highest specific activity of the enzymes. Lipase produced from three isolate have the optimum at pH 4, temperatures at 40-45 °C and stable in interesterification reaction (55 °C) for 30-40 min. HPLC analysis after interesterification enzymatic reaction in mixture palm kernel olein (PKOo) and palm stearin (POs) showed that the composition of triglycerides (TAG) do not change if compared with the commercial lipase (Lypozyme TL1M).